THE URGENCY OF FARDHU PRAYERS IN FORMING DISCIPLINE CHARACTER IN PRIMARY SCHOOL STUDENTS - Cisia Padila; Martin Kustati; Gusmirawati Gusmirawati (Fakultas Agama Islam Universitas Billfath, 2023)
This article discusses the crucial role of prayer (shalat) in shaping the discipline of elementary school students. Discipline is highly essential in molding the personalities of children from an early age. Prayer, as one of the religious practices in Islam, not only holds a religious dimension but also brings positive impacts in developing various aspects of character, especially discipline. Through literature review and empirical research, this article elaborates on how regular prayer implementation can serve as a means of shaping discipline in elementary school students. Prayer imparts values such as obedience, responsibility, and perseverance, all of which are key elements in forming discipline. Furthermore, the article explores the positive effects of prayer on the mental well-being of students. The concentration, tranquility of the mind, and self-control taught through prayer can directly contribute to the improvement of discipline in the school environment. The research includes interviews with teachers, parents, and elementary school students, as well as direct observations of prayer practices in their daily lives. The results indicate that students actively involved in prayer demonstrate higher levels of discipline compared to those who do not engage in religious activities. Thus, this article contributes to a deeper understanding of the urgency of prayer in the context of shaping discipline in elementary school students. The implications of these findings can serve as a foundation for the development of a more holistic character education program at the elementary school level, integrating religious values such as prayer as an integral part of the learning process.